2020
DOI: 10.1016/j.concog.2020.103024
|View full text |Cite
|
Sign up to set email alerts
|

Excessive use of reminders: Metacognition and effort-minimisation in cognitive offloading

Abstract: People often use external reminders to help remember delayed intentions. This is a form of "cognitive offloading". Individuals sometimes offload more often than would be optimal (Gilbert et al., 2020). This bias has been linked to participants' erroneous metacognitive underconfidence in their memory abilities. However, underconfidence is unlikely to fully explain the bias. An additional, previously-untested factor that may contribute to the offloading bias is a preference to avoid cognitive effort associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
37
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 43 publications
4
37
0
1
Order By: Relevance
“…This may be because cognitive effort is intrinsically costly [27,28]. Consistent with this, recent evidence shows that the bias towards reminders is reduced (but not eliminated) when participants receive financial compensation based on the number of points they score, which is hypothesized to increase cognitive effort [29]. Seeing as the participants in the present study received a fixed payment, regardless of their performance, it remains to be seen whether metacognitive interventions might be effective under conditions of performance-based reward.…”
Section: Plos Onementioning
confidence: 81%
See 1 more Smart Citation
“…This may be because cognitive effort is intrinsically costly [27,28]. Consistent with this, recent evidence shows that the bias towards reminders is reduced (but not eliminated) when participants receive financial compensation based on the number of points they score, which is hypothesized to increase cognitive effort [29]. Seeing as the participants in the present study received a fixed payment, regardless of their performance, it remains to be seen whether metacognitive interventions might be effective under conditions of performance-based reward.…”
Section: Plos Onementioning
confidence: 81%
“…Seeing as the participants in the present study received a fixed payment, regardless of their performance, it remains to be seen whether metacognitive interventions might be effective under conditions of performance-based reward. We also note that participants underwent the forced trials before the choice trials in this experiment, unlike previous studies where the two types of trial have generally been intermixed [11,29]. This could lead to inaccuracy in estimation of the reminder bias, if performance in the choice trials relative to forced trials was increased (e.g.…”
Section: Plos Onementioning
confidence: 99%
“…This study showed that a positive reminder bias can be observed in the context of both over-and under-confidence, indicating that one or more additional factors must be involved. Sachdeva and Gilbert (2020) provided evidence that one such factor is a preference to avoid cognitive effort.…”
Section: Intention Offloading and The Avoidance Of Cognitive Effortmentioning
confidence: 99%
“…As a result, individuals may prefer external reminders over internal memory because they incur a lower opportunity cost. Sachdeva and Gilbert (2020) argued that manipulating performance-based financial rewards allows a test of whether effort-avoidance influences intention offloading. If excessive use of reminders is explained by metacognitive error alone, then it should not matter whether or not performance is incentivised with financial reward.…”
Section: Intention Offloading and The Avoidance Of Cognitive Effortmentioning
confidence: 99%
“…Raising the costs of externalisations (e.g., by adding additional physical or temporal demands) increases the use of internal strategies such as memory-based processing, whereas lowering the costs of externalisations increases the use of technical tools (e.g., Cary & Carlson, 2001; Gray & Fu, 2004; Gray et al, 2006; Morgan & Patrick, 2013; O’Hara & Payne, 1998; Schönpflug, 1986). However, not all decisions to offload cognitive processes follow cost–benefit considerations of different strategies but may also be influenced by the current goals of the observers (Weis & Wiese, 2019) as well as their tendency to avoid demanding cognitive actions (Ballard et al, 1997; Kool et al, 2010; Sachdeva & Gilbert, 2020).…”
Section: Cognitive Offloadingmentioning
confidence: 99%